Association between conjunctival goblet cells and corneal resident dendritic cell density changes in new contact lens wearers. (18th August 2020) - Colorado, Luisa H; Pritchard, Nicola; Alzahrani, Yahya; Edwards, Katie; Efron, Nathan
Abstract : Background: To explore the interlink between conjunctival goblet and corneal dendritic cell density after six months of lens wear and to predict dendritic cell migration to the central cornea based on goblet cell loss in the conjunctiva as a response to contact lens wear. Methods: Sixty‐nine subjects who had never previously worn contact lenses were observed for six months; 46 were fitted with contact lenses and 21 served as a control group. Corneal confocal microscopy was used to quantify goblet and dendritic cell density before and after six months of daily lens wear. Symptomatic and asymptomatic groups were identified in the lens‐wearing group using a combination of signs and symptoms present. Pearson's correlation was used to determine associations between the total change of cell densities after six months of lens wear. Results: At baseline, there was no association between conjunctival goblet and corneal dendritic cell density (p > 0.05). After six months, there was an inverse association between the absolute change of conjunctival goblet and corneal dendritic cell density (ρ = −0.34, p = 0.03) in all participants (n = 69). Dendritic cell density in the central cornea was increased by 1.5 cells/mm 2 for every decrease of 1 goblet cell/mm 2 in the conjunctiva. Conclusions: After six months of wear, contact lens‐induced goblet cell loss can partially predict resident corneal dendritic cell migration to the central cornea (observed as an increase in dendritic cell density). The associations between total cell density change after six months was established in wearers regardless of lens symptomatology, suggesting that cell density changes as a physiological adaptation to regulate the effect of contact lens wear on the ocular surface.